«I do everything, but I don’t know how to make anything work»: Affective and relational learning of social media in later life - Roser BENEITO-MONTAGUT; Arantza BEGUERIA; Nizaiá CASSIÁN (Aula, 2018)
This exploratory paper argues that treating older adults learning as «representational knowledge» acquisition is not adequate if we want to understand how they learn to use digital technologies in general, and social media technologies in particular. Using examples taken from an ethnographic study exploring social media use in later life, the case is made for a range of digital practices and affective relations through which learning happens. The idea of communities of practice is a useful approach, however it also needs to be expanded to account for the practices that happened outside of the social and cultural centers and outside of the groups of interest formed around the interests in digital technologies. It is also useful to answer the question of how and why particular forms of «pedagogical authority» are enacted through particular digital practices, which are highly relational and affective, and how these forms of expertise become identity traits. We further discuss the implications of this for our understandings of identity and ageing within the digital society. Finally, we suggest that the term learning ecologies captures much better the practices of learning of older adults.